J.H. Johnston, Revised Charter and Ordinances of the City of Boonville, Mo. 44, art. 11, § 13 (1881) - (:unkn) unknown (General Publisher, 1881)
regulate the storage of gun powder and other combustible materials; and generally provide for the prevention of fires within the city.
--
Keywords: GUN POWDER STORAGE